Government Intervention and Business Response as Determinants of Business Continuity amid COVID-19: The Case of Jordan and Morocco - Anthony Fakhoury; Ali Fakih (Institute of Labor Economics (IZA), 2021)
This paper provides new insights into the role of governments and businesses in responding to pandemics in the Arab region. It uses the COVID-19 World Bank Enterprise Survey Follow-up dataset to examine the degree of business endurance in Jordan and Morocco amid the pandemic. Relying on the probit regressions, the empirical findings suggest that businesses that assumed resilient strategies such as establishing an online presence and converting production are more likely to remain open, whereas firms that adopted remote working are less likely to survive. This is due to the unpreparedness of firms and the limited availability of technologies in Jordan and Morocco for teleworking. Further, firms that expected future government supports are more likely to report closure. Finally, our results do not provide evidence that government grants and measures and the level of online sales are statistically significant in our model. The model used also offers further testable hypotheses for future research to comprehend the significance of the response of businesses to unprecedented shocks.
Keywords: H11; H12; O53; 330; business continuity; business response; government intervention; remote working; COVID-19; Jordan; Morocco